Focusing Properties of a Modified Retarding Structure for Linear Electron Accelerators - Vladimir Kuz'mich Shilov; Aleksandr Nikolaevich Filatov; Aleksandr Evgen'evich Novozhilov (International Journal of Electrical and Computer Engineering (IJECE), 2017)
When using accelerators in industry and medicine, important are the dimensions of the device used, especially the radial ones. In the linear electron accelerators based on a biperiodic retarding structure, which operates in the standing wave mode, there is a possibility to provide focusing of the accelerated particles with the help of high-frequency fields without the use of external focusing elements. In the accelerating cell, due to the presence of the far protruding drift sleeves, the electric field lines become strongly curved, which leads to the appearance in the regions adjacent to these sleeves of a substantial in magnitude radial component of the electric field. The particles entering the accelerating gap experience the action of a force directed toward the axis of the system, and at the exit, of a force directed away from the axis. Under certain conditions, alternation of the focusing and defocusing fields can lead to a general focusing effect. In the paper we study the focusing properties of a modified biperiodic structure with standing wave. The main attention is paid to the possibility of using the focusing properties of the electromagnetic accelerating field for guiding the electron beam through the aperture of the accelerating system, which will lead to a significant reduction in the accelerator sizes. The proposed method can be applied in the calculation and design of linear electron accelerators.